Undergraduate teaching and assessment methods in prosthodontics curriculum: An international Delphi survey. (August 2022) - Khalaf, Khaleel Al; Moore, Ciaran; McKenna, Gerry; Da Mata, Cristiane; Lynch, Christopher D.
Abstract: Objectives: To achieve consensus amongst an expert panel of prosthodontics/restorative dentistry academics on the best undergraduate teaching and assessments, and to develop recommendations regarding teaching and assessment of undergraduate prosthodontics. Methods: Semi-structured electronic questionnaires were used to collect data from senior clinical academics involved in the teaching of prosthodontics on three consecutive occasions (Delphi method). The questionnaires asked the experts' opinion on best teaching and assessment methods in the undergraduate prosthodontics curriculum. Invitation emails, with a hyperlink to the Round 1 questionnaire, were sent to 36 international dental academic experts. In later rounds, panellists were invited to consider their previous responses in light of the overall group response in attempt to bring the panel to a consensus. The group response was summarized using simple descriptive statistics, and the target level of consensus for each question was set at ≥ 70%. A response rate of at least 70% between rounds was deemed appropriate to maintain rigour. Results: Twenty-three senior academic experts from eleven countries agreed to participate. Eighteen (representing nine different countries) completed the questionnaires in its entirety (response rate 78.3%). The number of statements that attained consensus agreement was much higher than the number of non-consensus statements—92.6%, 175 statements out of 189 over three iterative rounds. Only 14 statements did not obtain a consensus during this Delphi study. Conclusions: A total of 175 consensus statements represent the agreement expert views of participated senior academics in prosthodontics from nine different countries and across four continents. These consensus statements could be considered detailed guidelines and recommendations to improve future undergraduates' curriculum in prosthodontics. Clinical significance: This Delphi study achieved a high consensus among a panel of senior academics in the teaching and assessment of undergraduate prosthodontics. This consensus could help minimise the current international and national divergence in dental schools' prosthodontics curricula, which could benefit future dentists and, subsequently, the patients.